Cannabis and cancer: unveiling the potential of a green ally in breast, colorectal, and prostate cancer - Husam A. ALSalamat; Sara Feras Abuarab; Hazem Mohamed Salamah; Anas Hasan Ishqair; Mohammad Fuad Dwikat; Anas Zakarya Nourelden; Aseel N. Qandil; Yasmeen Barakat; Muna Barakat (BMC, 2024)
Abstract Cancer comes in second place on the list of causes of death worldwide. In 2018, the 5-year prevalence of breast cancer (BC), prostate cancer (PC), and colorectal cancer (CRC) were 30%, 12.3%, and 10.9%, respectively. Cannabinoids are chemicals derived from the Cannabis sativa plant; the most investigated cannabinoids are cannabinol, delta 9-tetrahydrocannabinol (Δ9-THC), and cannabidiol. In humans, the endogenous endocannabinoid system consists of endocannabinoids, cannabinoids receptors (CBs), and enzymes that degrade the endocannabinoids. In this review, we will review the most recent literature for evidence that discusses the role of cannabis in the treatment of the three types of neoplasms mentioned. Studies have proved that BC cells express CB receptors; many in-vivo studies showed that cannabinoids cause apoptosis and inhibit proliferation and migration. Also, researchers found that treating BC mice with THC and JWH-133 (CB2 receptor agonist) slowed the tumor growth. Regarding CRC, cannabidiol was found to decrease the viability of chemotherapy-resistant CRC cells and inhibit metastasis by antagonizing the G-protein-coupled receptor 55 (GPR55; a novel cannabinoid receptor) necessary for metastasis. Moreover, cannabidiol had anti-angiogenetic effects by reducing the expression of vascular endothelial growth factor (VEGF) in addition to anti-inflammatory effects. Finally, studies demonstrated that PC cells highly express CB1 and CB2 receptors and that cannabinoids are capable of inhibiting the release of exosomes and microvesicles related to cancer progression. Cannabinoids also have antiproliferative, anti-invasive, anti-fibroblastic, cell cycle arrest, and proapoptotic effects on PC cells.